От генетики человека до генной терапии – эволюция понятий и терминов, знаний и практик - Пискун, Р.П.; Савицкая, Е.А.; Лилевская, А.А.; Климчук, И.Н. (Фактори експериментальної еволюції організмів, 2016)
Aim. Genetics is developing so rapidly that not only the general public, but also experts do not have time to keep an eye on changes of our ideas of the fundamental basis of life and heredity. Methods. Research, evolutionary-historical and bibliographical methods have been used. Results. It became clear that the functional processes in a cell are incredibly complex. They become extremely difficult in the whole multicellular organism. In these processes involved many of variable components that interact with each other, and form a multidimentional spatiotemporal network. Therefore, the final effect can not be deduced by mechanical addition of components. Therefore some concepts and terms have been introduced to concretize the volume of knowledge and practical use of them in a particular field of genetics – the science of heredity and variation of all living organisms. Conclusions. For the last decades genetics and molecular biology have accumulated a huge volume of information, which requires not just understanding but also review of concepts, on which the principles of understanding organization of living systems are based. Keywords: human genetics, medical genetics, clinical genetics, cytogenetics, gene therapy.